Reproducing women medicine, metaphor, and childbirth in late imperial China - Wu, Yi-Li, 1965-; American Council of Learned Societies (Berkeley : University of California Press, 2010)
"Uses the lens of cultural history to examine the development of med icine in Qing dynasty China. Focusing on the specialty of 'medicine for women' (fuke), Yi-Li Wu explores the material and ideological issues a ssociated with childbearing in the late imperial period. She draws on a rich array of medical writings that circulated in seventeenth- to nine teenth-century China to analyze the points of convergence and contentio n that shaped people's views of women's reproductive diseases."--Publis her description.
Late imperial fuke and the literate medical tradition -- Amateur as arbiter : popular fuke manuals in the Qing -- Function and structure in the female body -- An uncertain harvest : pregnancy and miscarriage -- "Born like a lamb" : the discourse of cosmologically resonant childbir th -- To generate and transform : strategies for postpartum health.
Includes bibliographical references (p. 319-342) and index.
Electronic text and image data.
Keywords: Childbirth -- China -- History; Women's health services -- History; China -- Social life and customs -- 1644-1912.